(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Political outreach of ward members in municipal corporations is core to the functioning of democracy at the gross root of democratic institutions. The 74th Constitutional Amendment Act set the seal on women’s participation in the urban local bodies, requiring them to participate effectively in the municipal corporation and its decision-making. This paper tries to present the factors that motivated and pulled back the women ward members from managing their reach and in the process of their decision-making in the municipal corporations of Andhra Pradesh. It focuses on the activity of the ward members in thecity wards, council meetings, and corporation activities. It highlight show the female ward members decide their responsibilities compared to the men. The paper presents some case studies of how women evolved from a de-facto member who contests the elections for family members to independent ward members and also aspires for better positions like Dy Mayors, Mayors, and more.